Google Earth Utilization in Increasing Spatial Literacy of High School Students - Hamdanah, Hilda; D, Rahmat; I, Setiawan (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This research is aim to (1) identify utilization of google earth in increasing spatial literacy of students. Spatial literacy is the ability of student in determine the location, distance, and space. (2) identify the response of students in using google earth to learn geography. Method that used in this research is literature study. The results of this research is the table of google earth utilization in creasing spatial literacy of student which includes the ability to determine the location, distance, and relation between space. As for the table that used was a table that has never been tested because that table was only from literature study of researcher as a recommendation for the future researchers